Nursing Care According to NANDA-I Diagnoses, NIC Interventions, and NOC Outcomes in a Patient with Autoimmune Encephalitis: A Case Report - Selda Çelik; Emine Ezgi Özçelik (Sakarya Üniversitesi Holistik Sağlık Dergisi)
Encephalitis, defined as inflammation of the brain tissue, is an uncommon yet serious condition that can lead to severe brain damage. Nursing care is critical in increasing the effectiveness of treatment in patients with encephalitis. In the case presented here, care was planned and implemented based on nursing diagnoses by field in the NANDA-I classification, NIC interventions, and NOC outputs. The patients’ nursing diagnoses were identified as ineffective health management, imbalanced nutrition: less than body requirements, fluid volume deficit, constipation, impaired physical mobility, impaired verbal communication, hopelessness, impaired social interaction, ineffective sexuality, risk for impaired psychological health, risk for ineffective activity planning, risk for impaired independent decision making, hyperthermia, chronic pain, and risk for delayed development. The care plan for four of these diagnoses is presented.